High-Throughput Sequencing Reveals the Regulatory Networks of Transcriptome and Small RNAs During the Defense Against Marssonina brunnea in Poplar - Liao, Yangwenke; Zhang, Qingyue; Cui, Rongrong; Xu, Xin; Zhu, Fuyuan; Cheng, Qiang; Li, Xiaogang (Frontiers in Plant Science, 2021)
MicroRNAs are implicated in the adjustment of gene expression in plant response to biotic stresses. However, the regulatory networks of transcriptome and miRNAs are still poorly understood. In the present study, we ascertained the induction of genes for small RNA biosynthesis in poplar defense to a hemibiotrophic fungus Marssonina brunnea and afterward investigated the molecular regulatory networks by performing comprehensive sequencing analysis of mRNAs and small RNAs in M. brunnea-inoculated leaves. Differentially expressed genes in M. brunnea-infected poplar are mainly involved in secondary metabolisms, phytohormone pathways, the recognition of pathogens, and MAPK pathway in the plant, with real-time quantitative PCR (qPCR) validating the mRNA-seq results. Furthermore, differentially expressed miRNAs, such as MIR167_1-6, MIR167_1-12, MIR171_2-3, MIR395-13, MIR396-3, MIR396-16, MIR398-8, and MIR477-6, were identified. Through psRobot and TargetFinder programs, MIR167-1-6, MIR395-13, MIR396-3, MIR396-16, and MIR398-8 were annotated to modulate the expression of genes implicated in transportation, signaling, and biological responses of phytohormones and activation of antioxidants for plant immunity. Besides, validated differentially expressed genes involved in lignin generation, which were phenylalanine ammonia-lyase, ferulate-5-hydroxylase, cinnamyl alcohol dehydrogenase, and peroxidase 11, were selected as targets for the identification of novel miRNAs. Correspondingly, novel miRNAs, such as Novel MIR8567, Novel MIR3228, Novel MIR5913, and Novel MIR6493, were identified using the Mireap online program, which functions in the transcriptional regulation of lignin biosynthesis for poplar anti-fungal response. The present study underlines the roles of miRNAs in the regulation of transcriptome in the anti-fungal response of poplar and provides a new idea for molecular breeding of woody plants.